Impact of pretreatment solution and temperature on drying of Cornelian cherry - Uz, S.; Doymaz, I. (PLAPIQUI(UNS-CONICET), 2024)
Cornus mas L. whose common name is Cornelian cherry, mostly lives in Southern Europe and Southwest Asia naturally. One of the most popular methods for increasing food stability is drying, which lowers water activity, minimizes physical and chemical alterations, and lowers microbiological activity while materials are being stored. The effective moisture diffusivity (De ff), activation energy (Ea), drying time, and drying rate were examined in relation to different drying temperatures. Pretreated (Sod. Hyd. and Potas) / untreated (Control) Cornelian cherry samples were dried at three different temperatures (55, 65, and 75 degrees C). Results of study presented that the drying behaviours of Cornelian cherries are affected by using pretreatment solution and change of air temperature. Six well-known mathematical models in the literature for thin layer drying processes were applied to the experimental moisture ratio values of Cornelian cherries. Regression analysis has demonstrated that the Midilli & K & uuml;& ccedil;& uuml;k model, which has the highest R2 value and the lowest RMSE and chi 2 values, is the best appropriate model to explain the drying behaviour. Fick's second law was used to calculate the De ff values. The calculated De ff values from 1.29 x 10-10 m2/s as a function of temperature increased by 5.47 x 10-10 m2/s. The Ea values are of 50.74 kJ/mol, 42.07 kJ/mol and 38.88 kJ/mol for in order of Control, Sod. Hyd. and Potas samples.
Keywords: Activation energy; Cornelian cherry; Drying; Effective moisture diffusivity; Mathematical modelling; QUALITY; FRUITS; Engineering